2016
DOI: 10.1038/cddis.2016.148
|View full text |Cite
|
Sign up to set email alerts
|

A ribosome-related signature in peripheral blood CLL B cells is linked to reduced survival following treatment

Abstract: We have used polysome profiling coupled to microarray analysis to examine the translatome of a panel of peripheral blood (PB) B cells isolated from 34 chronic lymphocytic leukaemia (CLL) patients. We have identified a ‘ribosome-related' signature in CLL patients with mRNAs encoding for ribosomal proteins and factors that modify ribosomal RNA, e.g. DKC1 (which encodes dyskerin, a pseudouridine synthase), showing reduced polysomal association and decreased expression of the corresponding proteins. Our data sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 65 publications
4
24
0
Order By: Relevance
“…Although such changes may reflect a mere necessity to sustain high protein synthesis rate and rapid cell proliferation, they may hold prognostic or predictive values. For example, translational profiling analysis of chronic lymphocytic leukemia (CLL) patients led to the identification of a 'ribosome-related translational signature' comprising RPs, translation initiation factors, and DKC1 100 . The authors connect decreased DKC1 expression observed in CLL with reduced synthesis of certain RPs, which in turn would promote translatome alteration and the acquisition of an aggressive phenotype.…”
Section: The Oncogenic Ribosomementioning
confidence: 99%
“…Although such changes may reflect a mere necessity to sustain high protein synthesis rate and rapid cell proliferation, they may hold prognostic or predictive values. For example, translational profiling analysis of chronic lymphocytic leukemia (CLL) patients led to the identification of a 'ribosome-related translational signature' comprising RPs, translation initiation factors, and DKC1 100 . The authors connect decreased DKC1 expression observed in CLL with reduced synthesis of certain RPs, which in turn would promote translatome alteration and the acquisition of an aggressive phenotype.…”
Section: The Oncogenic Ribosomementioning
confidence: 99%
“…The disease-specific translatome of unstimulated CLL has been determined by polysome profiling coupled to microarray analysis 16 to demonstrate reduction in ribosomal proteins compared with control B cells. However, broad application of the polysome-profiling approach is hindered by the technical difficulty of polysome fractionation, which does not cleanly resolve fractions that have more than a few ribosomes per transcript, and by the need to collect and analyze many fractions per sample.…”
Section: Introductionmentioning
confidence: 99%
“…While a large number of studies have deeply investigated the consequences triggered by DKC1 downregulation (reviewed by [5] ), to date, little is known about the effects of DKC1 overexpression, despite being well established that it represents a hallmark of many types of sporadic cancers [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] . In addition, DKC1 overexpression is associated with resistance to cancer-treating agents and tumor aggressiveness, and is thus considered a marker of poor prognosis [9] , [14] , [15] , [16] , [17] , [18] . It is worth noting that DKC1 encodes multiple minor splice isoforms [19] , [20] whose functions remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%